Utopia and Intellectual Humility: More, Bacon and Swift Appraising Law and Technology - Karen Schultz (Law, Technology and Humans)
Law and frontier technologies have been variously perceived in Western literature’s early classic utopias. Utopias’ diverse narratives and commentaries have applauded law’s interplay with technology or admonished it – utopias have variously imagined technological progress or pitfalls. Recently, given frontier technologies’ risk profiles, it has been suggested that a counter of intellectual humility should accompany their operation. Yet, intellectual humility is not a new awareness – its value, connecting with law and technology’s interplay, is illustrated in select utopias in the early Western literary tradition. This article’s consideration of a trilogy of select utopias proceeds in three big-picture strokes. First, it considers the interplay and intertextual connections of law and technology in three of the earliest British fictions in utopia’s ‘imagined travellers’ mode: Thomas More’s Utopia (1516); Francis Bacon’s New Atlantis (1626); and Jonathan Swift’s Gulliver’s Travels (1726). Second, this article recollects recent calls for ‘intellectual humility’ to accompany the development and operation of frontier technologies. However, intellectual humility lacks consensus – it can generally be expressed as reflecting approaches to measuring a sceptical mind that recognise fallibility and reject over-confidence. Third, each of the select utopias concerning law and technology’s interplay with intellectual humility is briefly considered. The texts are not straightforward: More, Bacon and Swift variously correlate the potential of human capacities with technological futures and offer various messages. While they extend optimistic reassurance that good judgment can exist, they offer pessimistic cautions – poor judgment on matters technological can bear terrible consequences. This article’s purpose is to deepen the discourse.